Profiling the Linear Peptides of Venom from the Brazilian Scorpion Tityus serrulatus: Structural and Functional Characterization - Dias, Nathalia Baptista; de Souza, Bibiana Monson [UNESP]; Cid-Alda, Fernanda; Dorce, Valquíria Abrão Coronado; Cocchi, Fernando Kamimura [UNESP]; Palma, Mario Sergio [UNESP] (American Chemical Society (ACS), 2024)
Scorpion venoms are a rich source of bioactive peptides, most of which are neurotoxic, with 30 to 70 amino acid residues in their sequences. There are a scarcity of reports in the literature concerning the short linear peptides found in scorpion venoms. This type of peptide toxin may be selectively extracted from the venom using 50% (v/v) acetonitrile. The use of LC-MS and MS/MS enabled the detection of 12 bioactive short linear peptides, of which six were identified as cryptides. These peptides were shown to be multifunctional, causing hemolysis, mast cell degranulation and lysis, edema, pain, and anxiety, increasing the complexity of the envenomation mechanism. Apparently, the natural functions of these peptide toxins are to induce inflammation and discomfort in the victims of scorpion stings.